Extracting bioactive compounds : (CRC Press, 2009)
The demand for functional foods and neutraceuticals is on the rise, leaving product development companies racing to improve bioactive compound extraction methods – a key component of functional foods and neutraceuticals development. From established processes such as steam distillation to emerging techniques like supercritical fluid technology, Extracting Bioactive Compounds for Food Products: Theory and Applications details the engineering aspects of the processes used to extract bioactive compounds from their food sources.